2011
DOI: 10.1096/fj.10-169029
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen increases nuclear respiratory factor 1 transcription by activating estrogen receptor β and AP‐1 recruitment to adjacent promoter binding sites

Abstract: Little is known about endogenous estrogen receptor β (ERβ) gene targets in human breast cancer. We reported that estradiol (E(2)) induces nuclear respiratory factor-1 (NRF-1) transcription through ERα in MCF-7 breast cancer cells. Here we report that 4-hydroxytamoxifen (4-OHT), with an EC(50) of ~1.7 nM, increases NRF-1 expression by recruiting ERβ, cJun, cFos, CBP, and RNA polymerase II to and dismissing NCoR from the NRF1 promoter. Promoter deletion and transient transfection studies showed that the estrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 73 publications
2
31
0
Order By: Relevance
“…E2F is better associated with transcriptional activation and, more recently, with histone H3K56 acetylation (57). NRF1 is well known for its role in mitochondrial function, but recently has been associated with the mediation of estrogen effects on ER␣ gene transcription (58), something that may be relevant to the current finding for specific effects of EB on DNA methylation at that site in intron 1. Finally, the intron 1 sequence also contained five STAT sites in our region of analysis, a finding that highlights the potential importance of this transcription factor in Esr1 regulation.…”
Section: Lifelong Epigenetic Changes In Esr1 Induced By Perinatal Edcmentioning
confidence: 77%
“…E2F is better associated with transcriptional activation and, more recently, with histone H3K56 acetylation (57). NRF1 is well known for its role in mitochondrial function, but recently has been associated with the mediation of estrogen effects on ER␣ gene transcription (58), something that may be relevant to the current finding for specific effects of EB on DNA methylation at that site in intron 1. Finally, the intron 1 sequence also contained five STAT sites in our region of analysis, a finding that highlights the potential importance of this transcription factor in Esr1 regulation.…”
Section: Lifelong Epigenetic Changes In Esr1 Induced By Perinatal Edcmentioning
confidence: 77%
“…We previously reported that E 2 and 4-OHT increased NRF-1 gene expression in MCF-7 breast cancer cells by activating ERα (Mattingly et al 2008) and ERβ (Ivanova et al 2011), respectively. Here we examined if E 2 or the selective estrogen receptor modulators (SERMs) 4-OHT and RAL regulate NRF-1 transcription in HUVECs.…”
Section: Resultsmentioning
confidence: 99%
“…Western blotting followed standard procedures (Ivanova et al 2011; Mattingly et al 2008). In brief, 30-40 μg of protein lysates (see individual Figures) were separated on 10 or 14 % SDS PAGE gels and electroblotted to PVDF membranes.…”
Section: Methodsmentioning
confidence: 99%
“…After aspiration of the PBS, the tissues were frozen at −80°C. The tissues were mechanical homogenized in ChIP buffer (Ivanova et al 2011) and genomic DNA was shared by sonication on ice. 300 μg of lysed extracts were incubated with anti-ERα (HC-20) antibody or normal rabbit IgG (both from Santa Cruz).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation